Social Capital and Its Effect on Labour Market (Mis)match: Migrants' Overqualification in Germany - Nancy Kracke; Christina Klug (Journal of International Migration and Integration, 2021)
If a person is overqualified in the sense that an employee's level of training exceeds the job requirements, then some human capital lies idle and cannot be converted into appropriate (monetary and non-monetary) returns. Migrants are particularly at risk of being overqualified in their employment; however, this phenomenon cannot be fully explained by differences in human capital or socio-economic characteristics. This paper examines whether social capital plays a decisive role in migrants' risk of overqualification in Germany. Using data from the German IAB-SOEP Migration Sample, we analyse the job search process of migrants to determine whether social networks influence their risk of being employed below their acquired educational level. We estimate logistic regression models and find that social capital influences the adequacy of migrants' jobs: We show that migrants are at a greater risk of overqualification if they use only informal job search strategies such as relying on friends or family members. Moreover, we find that homophilous migrant networks and jobs in employment niches are risk factors for overqualification. We conclude that the combination of informal job search modes and homophilous migrant networks leads to a comparably high risk for migrants of being overqualified in their employment in the German labour market.
Keywords: 300; Overqualification; Migrants; Social capital; Job search